2004
DOI: 10.1111/j.1469-7610.2004.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult outcome for children with autism

Abstract: Although outcome for adults with autism has improved over recent years, many remain highly dependent on others for support. This study provides some information on prognostic indicators, but more fine-grained research is needed into the childhood variables that are associated with good or poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
1,106
5
26

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,458 publications
(1,209 citation statements)
references
References 41 publications
47
1,106
5
26
Order By: Relevance
“…A recent cohort study that included 118 children with autism followed into adolescence reported more significant social impairment among females than males (Tonge & Einfeld, 2003). However, other studies have not found gender differences in language level, unusual verbal behaviors, or the level of repetitive behaviors (Howlin et al, 2004).…”
Section: Prevalence and Change In Autism Symptoms In Adolescence Andmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent cohort study that included 118 children with autism followed into adolescence reported more significant social impairment among females than males (Tonge & Einfeld, 2003). However, other studies have not found gender differences in language level, unusual verbal behaviors, or the level of repetitive behaviors (Howlin et al, 2004).…”
Section: Prevalence and Change In Autism Symptoms In Adolescence Andmentioning
confidence: 96%
“…Having mental retardation is frequently related to greater severity of autism symptoms, poorer overall outcome, and a decreased likelihood of improvement (Lord & Bailey, 2002;McGovern & Sigman, 2005;Nordin & Gillberg, 1998;Seltzer et al, 2004;Shea & Mesibov, 2005). Conversely, better language ability has been shown to be associated with both better contemporaneous functioning and a greater likelihood of improvement over time (Howlin, Goode, Hutton, & Rutter, 2004;Howlin et al, 2000;Lord & Bailey, 2002;Nordin & Gillberg, 1998;Seltzer et al, 2004;Shea & Mesibov, 2005). In terms of an association between gender and autism symptoms, findings are mixed.…”
Section: Prevalence and Change In Autism Symptoms In Adolescence Andmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may cause difficulties in a second domain of ER, situation modification, where one is able to alter a situation in order to regulate potential emotional responses. Individuals with ASD are known to have difficulties with naturalistic problem solving [Channon, Charman, Heap, Crawford, & Rios, 2001] and may have rigid ways of trying to cope with stressors to attain emotional relief [Howlin, Goode, Hutton, & Rutter, 2004].…”
Section: Modal Model Of Ermentioning
confidence: 99%
“…However, such studies as have singled out adults with high functioning ASD and presented data specifically related to their employment experiences have tended to show poor outcomes for this group. These include low rates of independent employment; jobs that are not commensurate with the individual's ability levels; and difficulty maintaining jobs (Howlin, Mawhood, & Rutter 2000;Romoser 2000;Howlin et al 2004;Hurlbutt & Chalmers 2004;Cederlund et al 2008;Stuart-Hamilton et al 2009;. In addition, it appears that many adults with high functioning ASD are not receiving the supports at work that they need in order to perform their jobs well (Beardon & Edmonds 2007).…”
mentioning
confidence: 99%